Nutritional Status And Post-cardiac Surgery Outcomes: An Updated Review With Emphasis On Cognitive Function - Norsham Juliana; Nur Adilah Shuhada Abd Aziz; Sofwatul Mokhtarah Maluin; Noor Anisah Abu Yazit; Sahar Azmani; Suhaini Kadiman; Kamilah Muhammad Hafidz; Nur Islami Mohd Fahmi Teng; Srijit Das (MDPI, 2024)
Journal of Clinical Medicine Volume 13